Town Rat and Country Rat - Fremont, Isabelle (University Press Plc, 2008)
The series includes books graded at six levels of language difficulty;the story in each grade are chosen to suit the age of the pupils for whom they are meant.
Keywords: Juvenile literature-Fiction